Analysis of the Benefits of Equine Therapy in Children with Cerebral Palsy (European Journal of Health Research, 2023)
Cerebral palsy in the child population encompasses alterations in motor functions, usually accompanied by other impairments in language and cognitive and sensory development. Complementary support therapies are a great ally in the treatment of minors, having been shown to improve psychosocial and behavioral skills and the general development of children with cerebral palsy. In this sense, equine therapy provides multiple benefits, both physically and psychologically. The aim of this work was to analyze the benefits of equine therapy and hippotherapy for children with cerebral palsy. For this, a systematic review was carried out on the articles published in the last 10 years in the Web of Science, PubMed, Tripdatabase and Cochrane databases. After applying the inclusion and exclusion criteria, 9 were finally selected. The studies found indicate that, among the multiple areas affected and that experience improvement with this type of therapy, the benefits that it reports to children on a physical level are high. . Among them are the improvement of the elimination pattern, body control and posture. And at a socio-psychological level, an increase in interest in the game, learning capacity, curiosity and communicative intention is noted, as well as an improvement in proprioception, attention and socialization skills. Therefore, this work highlights the advances generated by equine therapy in different areas of the life of minors with cerebral palsy.
Keywords: cerebral palsy; intellectual disability; horse therapy; equine therapy